2018
DOI: 10.5897/jmpr2018.6682
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and use of wild edible plants by migratory shepherds in the Himachal Pradesh of the Western Himalayas, India

Abstract: The present study was carried out in Himachal Pradesh of the Western Himalayas, India to obtain information on the wild edible plants used by the migratory shepherds. The shepherds started their migration in July from Chitkul, Rakchham, Batseri, Sangla and Kamru of district Kinnaur (Himachal Pradesh). Questionnaire for the survey, personal field visits and participatory observations were used to collect information about the use of various plants by the migratory shepherds. The shepherds move in a group of 5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Altogether, 58 WEPs were utilized in the study area. These values are well within the range of 32-72 WEPs reported from Jammu and Kashmir (Kumar and Hamal 2009;Dangwal et al 2014;Singh et al 2021), other parts of Indian Himalayas (Aryal et al 2018;Radha et al 2018;, Nepal Himalayas (Bhattarai et al 2009;Uprety et al 2012;Khakurel et al 2021), and the World (Alemnah 2020; Hegazy et al 2020;Purba and Silalahi, 2021;Ahmad et al 2022). However, some studies have reported very high number of WEPs in their studies; 335 WEPs were identified from Hunan, China (Zou et al 2011), 173 WEPs from Xishuanbanna valley, China (Ghorbani et al 2012), 159 WEPs from Heihe valley, China (Kang et al 2012), 111 WEPs from Bandipora, Jammu and Kashmir, India (Singh et al 2016), 90 WEPs from Udhampur, Jammu and Kashmir, India (Bhatia et al 2018), 117 WEPs from Uzbekistan (Khojimatov et al 2020), and 130 plants from Kishtwar region of Jammu and Kashmir, India (Thakur and Dutt 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Altogether, 58 WEPs were utilized in the study area. These values are well within the range of 32-72 WEPs reported from Jammu and Kashmir (Kumar and Hamal 2009;Dangwal et al 2014;Singh et al 2021), other parts of Indian Himalayas (Aryal et al 2018;Radha et al 2018;, Nepal Himalayas (Bhattarai et al 2009;Uprety et al 2012;Khakurel et al 2021), and the World (Alemnah 2020; Hegazy et al 2020;Purba and Silalahi, 2021;Ahmad et al 2022). However, some studies have reported very high number of WEPs in their studies; 335 WEPs were identified from Hunan, China (Zou et al 2011), 173 WEPs from Xishuanbanna valley, China (Ghorbani et al 2012), 159 WEPs from Heihe valley, China (Kang et al 2012), 111 WEPs from Bandipora, Jammu and Kashmir, India (Singh et al 2016), 90 WEPs from Udhampur, Jammu and Kashmir, India (Bhatia et al 2018), 117 WEPs from Uzbekistan (Khojimatov et al 2020), and 130 plants from Kishtwar region of Jammu and Kashmir, India (Thakur and Dutt 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly from Chamba district of Himachal Pradesh, 50 plant species of which 23 are herbs, 13 were trees, 2 were climbers, and 12 shrubs were used as ethno medicinal [4]. 50 species were used as wild edible plants which are in shepherds' route from high hills to low hills in the Kinnaur district of Himachal Pradesh [2].…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the Himalayas are known for rich biodiversity, especially for wild edible plants, which play an important role in meeting food demands. e rural inhabitants who mainly comprise of herders, shepherds, or other marginalized population use wild plants frequently for their livelihood [2]. e need is to understand the biodiversity for resource management of the Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…These medicinal plants were commonly used by migratory shepherds in the Churdhar Trillium govanianum, Urtica dioica, Valeriana jatamansi, etc. (Chauhan, 1999;Radha, 2018;Radha et al, 2018). The seasonal movement of shepherds is precise significant for the existence of the livestock in the tough environmental circumstances, including high temperature in the summertime at low elevations and analyzed and cold temperature in winter season at high hills.…”
Section: Resultsmentioning
confidence: 99%